Thiopurine-induced pancreatitis in inflammatory bowel diseases. (April 2015) - Ledder, Oren; Lemberg, Daniel A; Day, Andrew S
Abstract : Crohn's disease and ulcerative colitis are chronic inflammatory conditions affecting the gut and can present at any age with increased numbers of diagnoses seen in many countries in recent years. The thiopurine drugs, azathioprine and 6-mercaptopurine, are commonly used to maintain remission in Crohn's disease and ulcerative colitis; however, the use of these drugs may be limited by the development of pancreatitis in some individuals. Recent data indicate a genetic risk factor and provides a potential immune-mediated mechanism for thiopurine-induced pancreatitis. Management of thiopurine-induced pancreatitis requires exclusion of the triggering drug, which leads to prompt resolution of symptoms. This thiopurine side-effect may limit therapeutic options for future management of patients.